THE INFLUENCE OF SOCIAL MEDIA AND MARKET PLACE MARKETING ON CONSUMER BUYING INTEREST IN PT. JMS - Niken Herawati; Syahrial Addin; Lady Diana Warpindyastuti; Ayu Azizah; Aris Hidayat (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The advancement of digital technology has had a significant impact on the development of social media and marketplaces, where both can be effective platforms for promoting company products and attracting consumers if implemented properly. The purpose of this study is to determine the influence of social media and marketplace on consumer purchasing interest at PT JMS. This type of research is quantitative research with a sampling technique using probability sampling techniques, with a total of 93 respondents. Primary data in this study were collected by distributing questionnaires, and secondary data obtained from books, journals, and internet media. The data analysis techniques used were multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), hypothesis testing, and coefficient of determination using the SPSS program version 25.0. The results of this study indicate that partially, each variable, namely social media marketing strategies and marketplaces, has a positive and significant effect on consumer purchasing interest at PT. JMS, which is 62.5%, and the remaining 30.5% is influenced by other factors outside of that.